Faktor Risiko Lingkungan Kejadian ISPA Pada Balita di Wilayah Kerja Puskesmas Panambungan - Nur Hamdani Nur; Muharti Syamsul; Genoveva Imun (Unit Publikasi Ilmiah Perkumpulan Intelektual Madani Indonesia, 2021)
Acute respiratory infections (ARI) is a disease that attacks one or more parts of the respiratory tract from the nose to the alveoli or lung. This disease which is caused by various factors (multifactorial) is the top rank disease in Indonesia, and is the biggest cause (17%) of the death of children under five years (toddlers). This study aims to determine the environmental risk factors for the incidence of ARI in children under five in the working area of the Panambungan Health Center. This type of research uses an observational analytic study with a cross-sectional design with a sample of 88 respondents obtained by simple random sampling technique. Data analysis was performed by using chi-square test and the magnitude of the risk with the odds ratio value. The results of statistical tests showed that the use of anti-mosquito coils (p = 0.021; OR = 3.573), kitchen ventilation (p = 0.000; OR = 0.112), and smoking habits of family members significantly affected ARI cases on toddlers in the working area of Panambungan Health Center, Makassar in 2020. Meanwhile, bedroom ventilation (p = 0.538; OR = 0.570) and the type of house floor (p = 0.269; OR = 1.889) did not significantly affect ARI cases on toddlers in the working area of Panambungan Health Center, Makassar in 2020.